DAMPAK PENANAMAN MODAL TERHADAP PEMBANGUNAN ERA OTONOMI KHUSUS DI PAPUA - Sri Iin Hartini; Dwi Seno Wijanarko (Sekolah Tinggi Ilmu Hukum Awang Long, 2018)
Business is one of the world that cannot stand alone. A country will be develop if business of the world to work and develop. Business of the law to quickly develop and advance without to set by signs and rule to clear cannot profit in the end. Most aspects from various kinds in other world, also involved both directly and indrectly with the world of this business. In relation to the sometimes do not give a priority for business that ultimately make the effort to bow and follow signs and ofthen even prioritizing business so ignore rules that there has been. Happened Practice Monopoly and competition effort unhealthy in Indonesia look from the big efforts to mastery the practice of up to the downstream upstream. The Constitutions No. 5 of 1999 about The Prohibition Practice Monopoly and The Competition of Business Unhealthy, to hope able bind business of the world of Indonesia.The present of Constitutions No. 5 of 1999 as control tool social that is effort to keep the public interest and prevent practice monopoly and/ competition effort unhealthy create a climate conducive through the business setting competition a healthy and tried to create the effectiveness of and efficiency in business activities. The duty of CSBC are supervise the implementation of Constitutions, with supervision to hopefully the perpetrator effort to compete with healthy so that the economic activities can walk more efficient and gave the benefits to consumers widely. CSBC have authority among other: received reports from the public and/ from the perpetrators effort on suspicion of the practice monopoly and/ competition unhealthy effort; doing research on suspicion of the busines activities or action of the effort that can lead to the practice monopoly and competition unhealthy effort. In researching case suspicion of the practice monopoly and competition effort unhealthy by CSBC also the authority to fall sanctions administrative to the perpetrators effort to contravene of the Constitutions resistant Monopoly.